An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Keywords: appropriation; destructive mode of coordination; social integration